ANALISIS PENGARUH PENYAJIAN LAPORAN KEUANGAN DAERAH DAN AKSESBILITAS LAPORAN KEUANGAN DAERAH TERHADAP AKUNTABILITAS PENGELOLAN KEUANGAN DAERAH KABUPATEN NGADA - Matilde Meo; Suryaningsi (Jurnal Akuntansi Universitas Muhammadiyah Kupang, 2020)
The background in this study with the phenomenon observed in the development of the public sector today is the increasing demands for the implementation of public accountability by public sector organizations. Public institutions, both central and regional, are demanded for accountability, so that all government agencies are required to prepare strategic plans, measure performance and report by striving to provide the best services in a transparent and quality manner. This study aims to examine the effect of the presentation of regional financial reports and the accessibility of regional financial reports on the accountability of regional financial management either partially or simultaneously. Sources of data obtained from the results of respondents' answers to questionnaires that have been distributed. The population is the PPKAD office of Ngada Regency and the research sample consists of 40 staff from the secretariat, verification, budget, revenue and treasury fields. The method used in this research is descriptive method and quantitative method. The method of analysis uses multiple regression analysis. The results of this research hypothesis testing indicate that partially the presentation of regional financial reports and the accessibility of regional financial reports has a positive effect on the accountability of regional financial management. Simultaneous testing shows the presentation of regional financial reports and the accessibility of regional financial reports have a significant effect on the accountability of regional financial management.